How serious are serious game assessments of reading and reading-related skills? - Heikkilä, Riikka; Hautala, Jarkko; Rantanen, Vesa; Nieminen, Lea; Pocknell, Maija; Latvala, Juha-Matti; Richardson, Ulla (Human Technology, 2025)
Purpose: This study examined the validity of serious game–based assessments (SGAs) for measuring Finnish primary school children’s (Grades 1–4; n = 735) reading, spelling, and related cognitive skills. Methods: Performance in the digital SGAs was compared with corresponding paper-and-pencil tasks assessing word and pseudoword reading, sentence reading fluency, spelling, and underlying skills including phonological processing, rapid automatized naming, short-term memory, receptive vocabulary, and associative learning. Results: The SGAs showed good concurrent and construct validity for reading fluency, reading accuracy, spelling, rapid automatized naming, and vocabulary. The SGA tasks explained 72–80% of the variance in traditional reading fluency measures and 51–66% in reading accuracy. Conclusions: The findings indicate that serious game–based assessments provide a valid and engaging alternative to traditional literacy assessment tools. Implications for digital assessment and intervention in reading development are discussed.